The Lord of the Rings - Tolkien, J. R. R., author 578286 (London : Harper Collins Publishers, 2003)
The fellowship of the ring. Originally published: London: Allen & Unwin, 1954,The two towers. Originally published: London: Allen & Unwin, 1954. The return of the king. Originally published: London: Allen & Unwin, 1955